Grammatical Analysis of Pakistani Online Newspapers’ Representation: Comparison through Transitivity Analysis - Kazmi , Saira; Santosa, Riyadi; Efita Nur Rakhmawati , Deny (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
This study aimed to identify ideological bias behind two newspapers’ representation of the official visit to the US of former Prime Minister Imran Khan (21st to 24th July 2019), a visit which aimed to revive bilateral relations between the US and Pakistan. Data was collected from a mainstream newspaper, The News, and from an alternative one, Dawn. 11,734 words from eleven (11) news reports were analyzed in terms of transitivity (Halliday and Matthiessen, 2014) to interrogate the ‘context of culture’ and the ‘context of situation’ (Fairclough, 1995). The analysis of the data revealed that Imran Khan was chosen as a ’doer’ in the ‘Sayer’ role under the ’Verbiage’ participant role (van Leeuwen, 2005). Dawn portrayed Khan as the actor 53% of the time, while The News did so 44 % of the time, which can be said to communicate the newspapers’ ideological perspectives.